The role of envelope proteins in hepatitis B virus assembly. - Bruss, V (1991)
Hepatitis B virus (HBV) particles are generated by budding of preformed cytoplasmic nucleocapsids into endoplasmic reticulum (ER) membranes containing the three viral envelope proteins (L, M, and S). We have examined the contributions of the envelope proteins to virion assembly by using cultured hepatoma cells transfected with mutant HBV genomes bearing lesions in the envelope coding regions. We show here that HBV nucleocapsids are not released from cells without expression of envelope proteins, implying an active role for these proteins in viral morphogenesis. S and L but not M proteins are necessary for virion production. L protein over-expression inhibits virion release, just as it inhibits the release of subviral hepatitis B surface antigen (HBsAg) particles. Mutant L proteins that are no longer capable of retaining HBsAg particles in the ER still allow virion formation, indicating that this ER retention reaction is not required for viral budding. Myristoylation of L protein is also dispensable for virion formation. A chimeric protein bearing foreign epitopes fused to the S protein can be incorporated into virions when coexpressed with the wild-type envelope proteins. Models for the dependence of virion formation on both L and S proteins are discussed.